The Performance of Corn Husk with Rockwool and Egg Tray as Acoustic Panel - Zulkufli, Muhammad Firdaus Amin; Khairun Nizam, Muhammad Faris; Roslan, Muhammad Rifzal; Bujang, Hazirah; Mokhtar, Mardiha (Multidisciplinary Applied Research and Innovation, 2023)
The use of synthetic materials as acoustic absorbers is still applied in acoustical industries. These non-sustainable materials do not only cause contamination to the environment, but also contribute significantly in increasing the level of carbon dioxide which led to the effect of global warming. This project presents a way to find sustainable and eco-friendly materials to be an alternative sound absorber by using corn husks and egg tray as acoustic material, thus reduced the usage of synthetic materials such as rockwool. A sound absorber from corn husk, rockwool and egg tray is combined and its effectiveness is obtained through testing. Ten acoustic panels are tested by using Sound Level Meter test in an enclosure. The result show that the corn husks, rockwool and eggs tray have good performance in absorbing sounds. Furthermore, the testing in the enclosure with and without acoustic panels shows the difference in the percentage of sound intensity. The Corn Husk Acoustic Panel shows results in of sound intensity for about 2.18% and 3.16% in frequency of 500 Hz and 1000 Hz respectively when compared to presence with absence of acoustic panel. Lastly, the Corn Husk Acoustic Panel in this project compared with past research which used Grated Coconut Acoustic Panel. The acoustic panels then compared and it shows results on the difference in the percentage of intensity reduction. The Corn Husk Acoustic Panel shows results in sound intensity for about 39.73% lower and 18.51% lower in frequency of 500 Hz and 1000 Hz respectively when compared to Grated Coconut Acoustic Panel. The sound intensity lowered represents that the Corn Husk Acoustic Panel absorption is much better.